Factors Influencing Tax Avoidance: Corporate Governance, Profitability And Executive Character - Veronica Mithaulina; Cris Kuntadi (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2023)
Purpose –The purpose of writing this article is to build a hypothesis on the influence of corporate governance, profitability, and executive character on tax avoidance to be used in further research. Design/methodology/approach – This research was conducted through the study of theory and relationships or influences corporate governance, profitability, and executive character on tax avoidance from online books and journals sourced from Mendeley, Scholar Google and other online media. Findings –The results show that corporate governance has no effect on tax avoidance, while Return On Assets (ROA) and executive character have an effect on tax avoidance. Research limitations/implications –This study is only a literature review which is limited to research on the influence of corporate governance, profitability, and executive character variables on tax avoidance from various previous studies. Even though there are many other factors that influence tax avoidance Practical implications –This research suggests to study further and look for other factors that can affect tax avoidance besides corporate governance, profitability, and executive character. For example, company size, leverage, sales growth, company age, and capital intensity ratio. Originality/value – This research contributes to providing an understanding of tax avoidance and the factors that influence it.